An experimental study on vibration isolation performance of weft-knitted spacer fabrics. Issue 20 (December 2016) - Chen, Fuxing; Liu, Yanping; Hu, Hong
This paper presents an experimental study on the vibration isolation performance of weft-knitted spacer fabrics under forced harmonic excitation. The weft-knitted spacer fabrics with two different thicknesses were first designed by varying the linking distance of the spacer monofilament and fabricated using an electronic flat knitting machine. Then, their vibration isolation performance was tested under forced vibration condition via sinusoidal sweeps from low to high frequencies. The typical acceleration transmissibility curve and effects of fabric thickness, load mass and excitation level were discussed in detail. The results obtained show that the thicker spacer fabric has a lower resonance frequency than the thinner fabric due to lower stiffness, and thus can isolate the vibration at a lower frequency level. The results also show that changing the load mass and excitation level changes the loading conditions of the fabric structure, and thus also changes fabric stiffness and vibration isolation performance due to nonlinear behavior of spacer fabrics. It is expected that this study could provide some useful information to promote the application of weft-knitted spacer fabrics for vibration isolation.